Aplikasi konsep fizik dalam menyelesaikan masalah yang berasaskan stem bagi pelajar tingkatan enam atas - Lee, Jun Hung (2013)
The problem of students’ inability to apply physics concepts in solving STEM based problems is getting worse. The aims of this study are to determine the level of students’ interest in physics, level of students’ ability to applying physics concept, and constraints that students faced in applying physics concepts in solving STEM based problems. A total of 160 Form Six students from six secondary schools in Johor Bahru, Kulaijaya and Pontian participated in this study. The instruments used are STEM Based Physics Ability Test (STEM-FIZ), Questionnaires of Students’ Interest in Physics (MINFIZ) and interview. The data from MINFIZ and STEM-FIZ was analyzed quantitatively while the data from interview was analyzed qualitatively. The result from MINFIZ show that the students were interested in physics with an overall mean of 73.15 (SD = 10.21) while of STEM-FIZ shows a low level of student ability in applying physics concept in solving STEM based problems with a mean score of 41.7 (SD = 30.64). Pearson correlation analysis shows that there is a very low and not significant relationship (r = 0.109 and P = 0169) between the students’ interest in physics and the application of physics concepts in solving STEM based problems. The interview analysis shows that the constraints faced by the students in applying physics concepts in STEM based problems are the failure of students to master the concepts of physics and mathematics, methods of teaching and learning which are not student-centered, lack of review and discussion of students’ exercises. Thus, physics teachers should plan and implement a variety and student -centred teaching and learning methods so that the level of students applying physics concepts in solving STEM based problems can be enhanced.